A Comprehensive PCOS Research and Guideline Translation Program to Improve Practice - Ramasamy, Vijayanand A.; Garad, Rhonda M.; Boyle, Jacqueline A. (Seminars in Reproductive Medicine, 2021)
Polycystic ovary syndrome (PCOS) is a common and complex endocrinopathy affecting reproductive-age women with a reported prevalence of 8 to 13%. To address the knowledge, practice, consumer satisfaction, and research gaps, an international research collaboration was formed to develop the first “International Evidence-Based Guideline for the Assessment and Management of Polycystic Ovary Syndrome (2018).” This article describes an effective research translation program to disseminate the guideline internationally to women and health providers. To date, this had led to 75,197 views and almost 36,000 downloads of the PCOS guideline, and 43,000 views and 10,600 downloads of a suite of PCOS resources. AskPCOS app, the first freely accessible, evidence-based PCOS app, has 9,910 users (between 400 and 800 users per month), 23,447 sessions, and 87,801 screen viewings. Fifty-four percent of returning users are from across 137 countries, with the most users in Australia, the United States, the United Kingdom, the Netherlands, and India. Extensive global uptake of the PCOS guideline and compendium of resources was augmented by extensive formative consumer and health professional consultation, end-user engagement across the evidence-creation spectrum, co-design, and quality improvement.
Keywords: polycystic ovary syndrome; research translation; women's health; guideline